2017
DOI: 10.1371/journal.pgen.1006609
|View full text |Cite
|
Sign up to set email alerts
|

GWAS for serum galactose-deficient IgA1 implicates critical genes of the O-glycosylation pathway

Abstract: Aberrant O-glycosylation of serum immunoglobulin A1 (IgA1) represents a heritable pathogenic defect in IgA nephropathy, the most common form of glomerulonephritis worldwide, but specific genetic factors involved in its determination are not known. We performed a quantitative GWAS for serum levels of galactose-deficient IgA1 (Gd-IgA1) in 2,633 subjects of European and East Asian ancestry and discovered two genome-wide significant loci, in C1GALT1 (rs13226913, P = 3.2 x 10−11) and C1GALT1C1 (rs5910940, P = 2.7 x… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 59 publications
1
62
0
Order By: Relevance
“…Histopathologically, IgAN is characterized by mesangial cell proliferation with IgA-IC deposition in the glomerular mesangium, which is indistinguishable from pathologic findings of HSPN [2,12,14]. Regarding the pathogenesis of IgAN, several studies that investigated aberrant IgA1 O-glycosylation indicated that galactose-deficient IgA1 (Gd-IgA1) plays a pivotal role in the progression of IgAN [15][16][17][18][19][20][21][22][23]. According to these studies, patients with IgAN have aberrant IgA1 molecules with a Gal deficiency of O-linked glycans in the hinge region, which indicates that Gd-IgA1 consists of terminal N-acetyl-galactosamine (GalNAc) or sialylated GalNAc [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, IgAN is characterized by mesangial cell proliferation with IgA-IC deposition in the glomerular mesangium, which is indistinguishable from pathologic findings of HSPN [2,12,14]. Regarding the pathogenesis of IgAN, several studies that investigated aberrant IgA1 O-glycosylation indicated that galactose-deficient IgA1 (Gd-IgA1) plays a pivotal role in the progression of IgAN [15][16][17][18][19][20][21][22][23]. According to these studies, patients with IgAN have aberrant IgA1 molecules with a Gal deficiency of O-linked glycans in the hinge region, which indicates that Gd-IgA1 consists of terminal N-acetyl-galactosamine (GalNAc) or sialylated GalNAc [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent GWAS findings showed an association of IgAN with SNPs for critical glycosyltransferase and chaperone genes, C1GALT1 and COSMC. These data were validated with in vitro studies that revealed that 2 genome-wide significant loci, on chromosomes 7p21.3 and Xq24, influence Gd-IgA1 production [15,16]. Furthermore, environmental factors, such as mucosal infections, may further accentuate the aberrant O-glycosylation of IgA1.…”
Section: Discussionmentioning
confidence: 66%
“…These findings together suggested that elevated production of Gd-IgA1 in patients with IgAN was due to an abnormal biosynthesis in IgA1-secreting cells rather than galactose removal/degradation. This conclusion was further supported by 2 genome-wide association studies (GWAS) that implicated variants of C1GALT1 and COSMC in Gd-IgA1 serum levels [15,16].…”
Section: Introductionmentioning
confidence: 75%
“…It regulates the expression of thyroid-specific genes, including the NIS, TSHR, TG, and TPO. TTF1 usually plays an important role when it is biochemically and synergistically associated with Paired box gene 8 (46)(47)(48)(49)(50). Here, we revealed that TTF1 significantly up-regulates gene expression, cell proliferation, and migration in HTori3 cells, whereas these effects are attenuated by HECW1.…”
Section: Discussionmentioning
confidence: 90%